Application of Aspergillus oryzae and Rhizopus oryzae for Cu(II) removal - Huang, CP; Huang, CP (My University, 1996)
Biosorption of copper(II) by the untreated and acid-treated fungal biomass has been studied in both batch and column modes. Two species, Aspergillus oryzae and Rhizopus oryzae, were used in this study. A. oryzae mycelia (undergoing acid-washing) exhibit a clear advantage in Cu(II) removal, compared with other adsorbents. The acid-washing process can strongly enhance the adsorption capacity for A. oryzae mycelia. However, acid-washing does not alter the metal adsorption capacity of R. oryzae mycelia. The result indicates that acid-washing is not only a pretreatment step but also a regeneration step in the heavy metal removal process. These dual purposes, therefore, give the acid-washing biomass an indication of successful prospect. Cultivating A. oryzae in pellet form is an effective means of mycelium immobilization. The method established in this study provides the high-yield, uniformly-sized particles (2-3 mm in diameter), which are effective in solid-liquid separation. This pellet column can completely remove metals before breakpoint. After the breakpoint, a significant amount of Cu(II) removal over a long period has been observed. This is thought to be the result of intracellular uptake. Copyright (C) 1996 Elsevier Science Ltd
Keywords: fungi; copper; adsorption; Aspergillus oryzae; Rhizopus oryzae; heavy metal; immobilization